Surgery as an Adjunctive Treatment for Multidrug-Resistant Tuberculosis: An Individual Patient Data Metaanalysis - Fox, Gregory J; Mitnick, Carole D; Benedetti, Andrea; Chan, Edward D; Becerra, Mercedes; Chiang, Chen-Yuan; Keshavjee, Salmaan; Koh, Won-Jung; Shiraishi, Yuji; Viiklepp, Piret; Yim, Jae-Joon; Pasvol, Geoffrey; et al. (Clinical infectious diseases, 2016)
Medical treatment for multidrug-resistant (MDR)-tuberculosis is complex, toxic, and associated with poor outcomes. Surgical lung resection may be used as an adjunct to medical therapy, with the intent of reducing bacterial burden and improving cure rates. We conducted an individual patient data metaanalysis to evaluate the effectiveness of surgery as adjunctive therapy for MDR-tuberculosis. Individual patient data, was obtained from the authors of 26 cohort studies, identified from 3 systematic reviews of MDR-tuberculosis treatment. Data included the clinical characteristics and medical and surgical therapy of each patient. Primary analyses compared treatment success (cure and completion) to a combined outcome of failure, relapse, or death. The effects of all forms of resection surgery, pneumonectomy, and partial lung resection were evaluated. A total of 4238 patients from 18 surgical studies and 2193 patients from 8 nonsurgical studies were included. Pulmonary resection surgery was performed on 478 patients. Partial lung resection surgery was associated with improved treatment success (adjusted odds ratio [aOR], 3.0; 95% confidence interval [CI], 1.5-5.9; I(2)R, 11.8%), but pneumonectomy was not (aOR, 1.1; 95% CI, .6-2.3; I(2)R, 13.2%). Treatment success was more likely when surgery was performed after culture conversion than before conversion (aOR, 2.6; 95% CI, 0.9-7.1; I(2)R, 0.2%). Partial lung resection, but not pneumonectomy, was associated with improved treatment success among patients with MDR-tuberculosis. Although improved outcomes may reflect patient selection, partial lung resection surgery after culture conversion may improve treatment outcomes in patients who receive optimal medical therapy.